Manajemen Perubahan Organisasi: Strategi Efektif dalam Menghadapi Tantangan Global - Aramiko Kayanie Nenden Atryana; B. Herawan Hayadi; Furtasan Ali Yusuf; Devi Delawati; Irawati Irawati; Wiwik Novianawati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
Effective change management requires five main steps: assessing the situation, planning the change, putting the plan into practice, analyzing the results, and ensuring that the change is safe and effective in the organization. This research is in-depth about “Organizational Change Management: Effective Strategies in Facing Global Challenges.” Through the literature study method, this research examines more deeply how to implement an effective change management strategy to face an era of boundless global competition characterized by rapid changes in the business environment and advances in communication and information technology. In this effective strategy, it is necessary to involve employees and leaders who change the paradigm of thinking to face the rapid changes in the business environment in global competition for the success of the transformation.